Regression of gastric lymphoma of mucosa-associated lymphoid tissue with antibiotic therapy for Helicobacter pylori - Weber, D.M.; Dimopoulos, M.A.; Anandu, D.P.; Pugh, W.C.; Steinbach, G. (Gastroenterology, 1994)
Regression of low-grade B cell gastric lymphoma of mucosa-associated lymphoid tissue after eradication of Helicobacter pylori with antibiotic therapy was recently shown in a small number of patients with low-volume tumors. A patient with a > 10 cm nodular gastric mucosa-associated lymphoid tissue lymphoma that caused hematemesis and weight loss is described. Antibiotic therapy of H. pylori resulted in full clinical recovery and resolution of the mass lesion and morphological features of lymphoma on routine histological examination. However, monotypic immunostaining of plasma cells persisted in a separate and grossly normal-appearing region of the stomach. Antibiotic therapy may be of benefit in patients with mucosa-associated lymphoid tissue lymphoma with mass lesions and significant signs and symptoms, but periodic search for residual lymphoma is needed. © 1994.